Políticas curriculares para o ensino médio: os desafios da integração curricular para a construção do conhecimento e protagonismo do estudante - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
This dissertation is the result of a research proposal whose object of study analyzed the educational policies consolidated in the recent approval of the National Common Curricular Base (BNCC) and its relationship in the construction of knowledge considering the pragmatic aspect in the production of school policies for high school. As a public policy, the reformulation of the curriculum for high school sought to leverage mechanisms of technology in the fields of information and communication, which in contemporary times "fetishizes" the main human relationships, involving education, environment and consumerism in a complex scenario of society resulting from experiencing and human subjectivity. From the systematization of the object, the main problem was undertaken: how will the educational policy guided by the National Common Curricular Base enable the construction of knowledge and the learning protagonism of students in the context of the “new secondary education” that prioritizes the development of pragmatic and utilitarian competences? Thus, as a general objective, we intend to analyze the development of curricular policies and the integrating principles expressed in the BNCC for high school in schools of the state education network in the municipality of Amazonas. The specific objectives seek to analyze the curricular remodeling, emphasizing the explicit integrating principles both in the BNCC reciprocal to the New High School (NEM), but also, specifically, the relations in the historical, educational-local process, the development of contents and the performance of teachers in the implementation of the policy itself. From this perspective, the policy cycles approach is anchored in Stephen Ball (collaborators), Mainardes, Mainardes; Tello, developing the scenarios of influence, text production and field of practice, and through the theory of policy enactment, founds the field of teaching activity (Ball, Maguire, Braun, Mainardes, Tello) and within the curriculum integrated in Alice Lopes. The policy cycle approach was based on the methodology outlined in documentary research, an instrument for data collection and analysis, developed in two high schools in the city of Manaus-Amazonas, of the state education system, with twelve teachers from reference areas who work in the operationalization of the “new model” of curriculum. The results show schools as reproducers of educational policies, as they only legitimize the normative documents, where they prioritized the pragmatism and utilitarianism of the curriculum, resuming technicist teaching in a contemporary guise of society, which integrating competences and skills will need to add categories such as flexibility, technology and interdisciplinarity to the performativity of the teaching field. Finally, the reproduction of policies does not allow the learning protagonism of the secondary education student, so that the school proposals promote educational dualism, retroactions and social injustice. Keywords: Policy cycle. Educational politics. Integrated curriculum. High school.

Esta disertación es el resultado de una propuesta de investigación cuyo objeto de estudio analizó las políticas educativas consolidadas en la reciente aprobación de la Base Nacional Común Curricular (BNCC) y su relación en la construcción del conocimiento considerando el aspecto pragmático en la producción de políticas escolares para escuela secundaria. Como política pública, la reformulación del currículo para el bachillerato buscó aprovechar mecanismos de la tecnología en los campos de la información y la comunicación, que en la contemporaneidad “fetichiza” las principales relaciones humanas, involucrando educación, medio ambiente y consumismo en un escenario complejo de sociedad resultante del experimentar y de la subjetividad humana. A partir de la sistematización del objeto, se abordó el problema central: ¿cómo la política educativa orientada por la Base Curricular Común Nacional posibilitará la construcción del conocimiento y el protagonismo del aprendizaje de los estudiantes en el contexto de la “nueva educación secundaria” que prioriza el desarrollo de las competencias pragmáticas y utilitarias? Así, como objetivo general, pretendemos analizar el desarrollo de las políticas curriculares y los principios integradores expresados en la BNCC para la enseñanza media en las escuelas de la red estatal de educación en el municipio de Amazonas. Los objetivos específicos buscan analizar la remodelación curricular, enfatizando los principios integradores explícitos tanto en la BNCC recíproca a la Nueva Escuela Secundaria (NEM), como también, específicamente, las relaciones en el proceso histórico, educativo-local, el desarrollo de contenidos y el desempeño de los docentes en la implementación de la política misma. Desde esta perspectiva, el enfoque de los ciclos de política se ancla en Stephen Ball (colaboradores), Mainardes, Mainardes; Tello, desarrollando los escenarios de influencia, producción de textos y campo de práctica, y a través de la teoría de la promulgación de políticas, funda el campo de la actividad docente (Ball, Maguire, Braun, Mainardes, Tello) y dentro del currículo integrado en Alice Lopes. El enfoque del ciclo de políticas se basó en la metodología delineada en la investigación documental, instrumento de recolección y análisis de datos, desarrollado en dos escuelas secundarias de la ciudad de Manaus-Amazonas, del sistema educativo estatal, con doce profesores de las áreas de referencia que actúan en la operacionalización del “nuevo modelo” de currículo. Los resultados muestran a las escuelas como reproductoras de políticas educativas, pues solo legitiman los documentos normativos, donde priman el pragmatismo y el utilitarismo del currículo, retomando la enseñanza tecnicista en la sociedad contemporánea, que integrando competencias y habilidades necesitará agregar categorías como como flexibilidad, tecnología e interdisciplinariedad a la performatividad del campo docente. Finalmente, la reproducción de políticas no permite el protagonismo del aprendizaje del estudiante de educación secundaria, por lo que las propuestas escolares promueven el dualismo educativo, las retroacciones y la injusticia social. Palabras clave: Ciclo de políticas. Política educativa. Currículo integrado. Escuela secundaria.
Keywords: Base Nacional Comum Curricular; Educação integral; Currículos; Ensino médio - Amazonas; CIENCIAS HUMANAS; Ciclo de políticas; Política educacional; Currículo integrado; Ensino médio